2021
DOI: 10.1007/s12264-021-00759-9
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of Human Cortical Oligodendrocytes and Astrocytes

Abstract: Human cortical radial glial cells are primary neural stem cells that give rise to cortical glutaminergic projection pyramidal neurons, glial cells (oligodendrocytes and astrocytes) and olfactory bulb GABAergic interneurons. One of prominent features of the human cortex is enriched with glial cells, but there are major gaps in understanding how these glial cells are generated. Herein, by integrating analysis of published human cortical single-cell RNA-Seq datasets with our immunohistochemistical analyses, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(85 citation statements)
references
References 109 publications
7
74
0
Order By: Relevance
“…The LGE consists of subdomains including the dorsal LGE (dLGE) and vLGE (Wen et al, 2021;Yun et al, 2001). The progenitors located in the dLGE contribute to the olfactory bulb (OB) interneurons, whereas vLGE progenitors mainly generate striatal MSNs (Li et al, 2017(Li et al, , 2021Song et al, 2021;Waclaw et al, 2006Waclaw et al, , 2009Xu et al, 2018;Yang et al, 2021a;Zhang et al, 2016). In the Meis2-CKO at E16.5 the dLGE marker Sp8 was expanded ventrally, but the expression of Etv1 (another dLGE marker) was not significantly altered (Fig.…”
Section: Meis2 Is Required For the Differentiation Of The Olfactory B...mentioning
confidence: 99%
“…The LGE consists of subdomains including the dorsal LGE (dLGE) and vLGE (Wen et al, 2021;Yun et al, 2001). The progenitors located in the dLGE contribute to the olfactory bulb (OB) interneurons, whereas vLGE progenitors mainly generate striatal MSNs (Li et al, 2017(Li et al, , 2021Song et al, 2021;Waclaw et al, 2006Waclaw et al, , 2009Xu et al, 2018;Yang et al, 2021a;Zhang et al, 2016). In the Meis2-CKO at E16.5 the dLGE marker Sp8 was expanded ventrally, but the expression of Etv1 (another dLGE marker) was not significantly altered (Fig.…”
Section: Meis2 Is Required For the Differentiation Of The Olfactory B...mentioning
confidence: 99%
“…Recent single‐cell sequencing analyses suggest that EGFR signaling is more likely to be the relevant developmental pathway for the initiation of gliogenesis. EGFR is selectively upregulated in the cortical VZ/SVZ during later embryonic phase (Li et al., 2021; Yang et al., 2021), with its spatiotemporal expression pattern coinciding with the switch from neurogenesis to gliogenesis (Fox & Kornblum, 2005; Kornblum et al., 1997). Previous studies showed that SVZ NPCs expressing low Egfr level differentiate into oligodendrocytes, whereas those expressing high Egfr level differentiate into astrocytes (Burrows et al., 1997).…”
Section: Developmental Origin Of Astrocytesmentioning
confidence: 99%
“…Similarly, in rat postnatal cortex, the proliferation rate of APCs increases from P1 to P10 and then declines gradually (Moroni et al., 2018). In human cortex, a large number of bMIPCs that express EGFR , ASCL1 , and OLIG1/2 are generated at around GW23, and they continue to divide several rounds before they generate APCs (Yang et al., 2021). The APC proliferation probably persists for a long time after birth to keep up with brain growth.…”
Section: Developmental Origin Of Astrocytesmentioning
confidence: 99%
“…Despite this challenge, recent progresses have been made in our understanding of the generation of cortical astrocyte diversity in the human brain. By combining analysis of published human cortical single-cell RNA-Seq datasets with immunostainings performed on human fetal brain samples collected around mid-gestation, Yang and collaborators showed that cortical astrocytes, along with oligodendrocytes and olfactory bulb interneurons, were born from basal multipotent intermediate progenitors (bMIPCs) expressing EGFR, ASCL1, OLIG2, and OLIG1 ( Yang et al, 2022 ). Interestingly these bMIPCs are also found in the mouse brain ( Li et al, 2021 ) and thus seems to be a common feature of cortical astrocyte development from these two species.…”
Section: Discussionmentioning
confidence: 99%